High Possibility Classrooms as a pedagogical framework for technology integration in classrooms: an inquiry in two Australian secondary schools*. Issue 5 (20th October 2017) - Hunter, Jane
Abstract: Understanding how well teachers integrate digital technology in learning is the subject of considerable debate in education. High Possibility Classrooms (HPC) is a pedagogical framework drawn from research on exemplary teachers' knowledge of technology integration in Australian school classrooms. The framework is being used to support teachers who teach various stages of schooling to take 'pedagogical steps' in their practice with technology. This article focuses on the use of the HPC conceptual framework in a study of seven teachers and their students at two secondary schools in New South Wales, Australia. Analysis confirms the practicality of this conceptual framework for technology integration in secondary school classrooms. This inquiry has implications for addressing the reluctance of teachers to integrate technology in curriculum. The article concludes by suggesting that more schools might consider using conceptual frameworks like HPC to support secondary school teachers to enhance student learning with technology.